2020
DOI: 10.1101/2020.06.25.170464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis and Visualization of Sleep Stages based on Deep Neural Networks

Abstract: AbstractAutomatic sleep stage scoring based on deep neural networks has come into focus of sleep researchers and physicians, as a reliable method able to objectively classify sleep stages, would save human resources and thus would simplify clinical routines. Due to novel open-source software libraries for Machine Learning in combination with enormous progress in hardware development in recent years a paradigm shift in the field of sleep research towards automatic diagnostics co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…In addition, state-of-the-art deep learning approaches may be used as a tool for analyzing brain data, e.g. for creating so-called embeddings of the raw data [122]. Moreover, as proposed by Kriegeskorte [123], our neural corpus can serve to test [124] computational models of brain function [125][126][127][128], in particular models based on neural networks [129][130][131] and machine learning architectures [132,133], in order to iteratively increase biological and cognitive fidelity [123].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, state-of-the-art deep learning approaches may be used as a tool for analyzing brain data, e.g. for creating so-called embeddings of the raw data [122]. Moreover, as proposed by Kriegeskorte [123], our neural corpus can serve to test [124] computational models of brain function [125][126][127][128], in particular models based on neural networks [129][130][131] and machine learning architectures [132,133], in order to iteratively increase biological and cognitive fidelity [123].…”
Section: Discussionmentioning
confidence: 99%
“…We conclude, that while the non-linear effect of the softmax function might be desirable in a classification problem, it (partially) discards continuous patterns in the data that might be of medical relevance as well. Other work has presented a finding in the same direction [33], by showing that class separability (related to discreteness) in an automatic sleep staging model highly increased after the last softmax activation. In future work, one might therefore consider other normalizing functions in the classifier, that may replace this (non-linear) softmax function [34].…”
Section: Discussionmentioning
confidence: 62%
“…In this research, we did not research influences of design choices like data window length (which was fixed to 30 s), depth and width of the models, and the number and type of measurement channels used. Regarding the latter, the authors of [33] visually depicted (supervised) hypnodensities predictions on one EEG channel only, and showed that predictions did not drastically differ dependent on the chosen channel. However, visual inspection seemed to reveal that their singlechannel hypnodensities yielded higher entropy than the presented hypnodensities in this work and in [1].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, state-of-the-art deep learning approaches may be used as a tool for analysing brain data, e.g. for creating so-called embeddings of the raw data (Krauss et al, 2020). Moreover, as proposed by Kriegeskorte and Douglas (2018), our neural corpus can serve to test (Schilling et al, 2018) computational models of brain function (Krauss et al, 2017(Krauss et al, , 2016Schilling, Tziridis, et al, 2020), in particular models based on neural networks (Krauss, Prebeck, et al, 2019;Krauss, Schuster, et al, 2019;Krauss, Zankl, et al, 2019) and machine learning architectures (Gerum et al, 2020;Schilling, Gerum, et al, 2020), in order to iteratively increase biological and cognitive fidelity (Kriegeskorte & Douglas, 2018).…”
Section: Discussionmentioning
confidence: 99%